We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
92
1
avatar

I cant figure out the answer

 Feb 28, 2019
 #1
avatar+102461 
+2

This is just a substitution question.

 

\(x_{n+1}=(x_n)^2-x_n\\ so\\ x_{2}=(x_1)^2-x_1\\ If \;\; x_1=1\\ then\; x_{2}=(1)^2-1=0\\ \)

 

You can do the others yourself!

 Feb 28, 2019

8 Online Users

avatar